2014
DOI: 10.1371/journal.pone.0090746
|View full text |Cite
|
Sign up to set email alerts
|

Optical Metabolic Imaging of Treatment Response in Human Head and Neck Squamous Cell Carcinoma

Abstract: Optical metabolic imaging measures fluorescence intensity and lifetimes from metabolic cofactors nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD). These molecular level measurements provide unique biomarkers for early cellular responses to cancer treatments. Head and neck squamous cell carcinoma (HNSCC) is an attractive target for optical imaging because of easy access to the site using fiber optic probes. Two HNSCC cell lines, SCC25 and SCC61, were treated with Cetuximab (anti-EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 39 publications
6
63
0
Order By: Relevance
“…This decrease was caused by transition to more glycolytic metabolism. It was demonstrated on oral cancer cells (SCC25 and SCC61) in vitro that NADH/FAD redox ratio decreased after treatment of cells with Cisplatin [74]. Similar results were obtained on bladder cancer cell line (Т24).…”
Section: Redox Ratio As Metabolic Status Indicatorsupporting
confidence: 72%
See 1 more Smart Citation
“…This decrease was caused by transition to more glycolytic metabolism. It was demonstrated on oral cancer cells (SCC25 and SCC61) in vitro that NADH/FAD redox ratio decreased after treatment of cells with Cisplatin [74]. Similar results were obtained on bladder cancer cell line (Т24).…”
Section: Redox Ratio As Metabolic Status Indicatorsupporting
confidence: 72%
“…For example, decreased percentage reviews contribution of bound NADH and FAD, as compared to normal epithelial cells, was revealed on head and neck cancer cell cultures SCC25 and SCC61 [74]. The same work demonstrates increased contribution of bound NADH and FAD after treatment with chemotherapeutic agents Cisplatin, Cetuximab and BGT226.…”
Section: Nadh and Fad Fluorescence Lifetime In Energy Metabolism Evalmentioning
confidence: 69%
“…An instrument response function (IRF) was measured using the second-harmonic generated signal from a urea crystal, then deconvolved from the acquired sample decays. The timeresolved data was fit to a two-component exponential decay as described in previously published work, to model the distinct short and long fluorescence lifetimes of free and protein-bound NAD(P)H and FAD [13,14,16]. The fit model is I(t) = α 1 exp -t/τ 1 + α 2 exp -t/τ 2 + C, where I(t) is the time-resolved fluorescence intensity following the excitation pulse from the laser, α 1 and α 2 denote the relative contributions of the short and long lifetime components to the overall decay, and τ 1 and τ 2 are the short and long lifetime values.…”
Section: Methodsmentioning
confidence: 99%
“…NAD(P)H and FAD are autofluorescent metabolic co-enzymes. The ratio of the fluorescence intensities of NAD(P)H to FAD is the "optical redox ratio," which is sensitive to malignancy, tumor aggressiveness, and drug response [12][13][14][15][16][17][18]. In fact, changes in the redox ratio induced by anti-cancer drugs predict in vivo tumor response long before changes in tumor volume can be measured [15].…”
Section: Introductionmentioning
confidence: 99%
“…Error bars indicate calculated standard deviations [107]. [108] found redox ratio calculated inversely as NADH/FAD to be increased in cancerous colonic biopsies and malignant cell lines respectively. In vivo studies conducted by Walsh et al in mouse xenograft models for breast cancer [109] and Edward et al in oral cancer models in hamsters [90] also showed similar findings.…”
Section: Metabolic Assessment Of Normal Versus Cancer Cellsmentioning
confidence: 99%